The Impact of Age and BMI on the VWF/ADAMTS13 Axis and Simultaneous Thrombin and Plasmin Generation in Hospitalized COVID-19 Patients - Thangaraju, Kiruphagaran; Katneni, Upendra; Akpan, Imo J.; Tanaka, Kenichi; Thomas, Tiffany; Setua, Saini; Reisz, Julie A.; Cendali, Francesca; Gamboni, Fabia; Nemkov, Travis; Kahn, Stacie; Wei, Alexander Z.; et al. (Frontiers in Medicine, 2022)
Abstract Aging and obesity independently contribute towards an endothelial dysfunction that results in an imbalanced VWF to ADAMTS13 ratio. In addition, plasma thrombin and plasmin generation are elevated and reduced, respectively, with increasing age and also with increasing body mass index (BMI). The severity risk of Corona Virus Disease 2019 (COVID-19) increases in adults older than 65 and in individuals with certain pre-existing health conditions, including obesity (>30 kg/m2). The present cross-sectional study focused on an analysis of the VWF/ADAMTS13 axis, including measurements of von Willebrand factor (VWF) antigen (VWF:AG), VWF collagen binding activity (VWF: CBA), Factor VIII, ADAMTS13 antigen, and ADAMTS13 activity, in addition to thrombin and plasmin generation potential, in a demographically diverse population of COVID-19 negative (-) (n= 288) and COVID-19 (+) (n=543) patient plasmas collected at the time of hospital presentation. Data were analyzed as a whole, and then after dividing patients by age (<65 and ≥65) and independently by BMI (<18.5, 18.5-24.9, 25-29.9, >30 (kg/m2)). These analyses suggest that VWF parameters (i.e., the VWF/ADAMTS13 activity ratio and thrombin and plasmin generation) differed in COVID-19 (+), as compared to COVID-19 (-) patient plasma. Further, age (≥65) more than BMI contributed to aberrant plasma indicators of endothelial coagulopathy. Based on these findings, evaluating both the VWF/ADAMTS13 axis, along with thrombin and plasmin generation, could provide insight into the extent of endothelial dysfunction as well as the plasmatic imbalance in coagulation and fibrinolysis potential, particularly for at-risk patient populations.